Peripapillary Scleral Bowing Increases with Age and Is Inversely Associated with Peripapillary Choroidal Thickness in Healthy Eyes - Wang, Ya Xing; Yang, Hongli; Luo, Haomin; Hong, Seung Woo; Gardiner, Stuart K.; Jeoung, Jin Wook; Hardin, Christy; Sharpe, Glen P.; Nouri-Mahdavi, Kouros; Caprioli, Joseph; Demirel, Shaban; Girkin, Christopher A.; et al. (American journal of ophthalmology, 2020)
PURPOSE: To use optical coherence tomography (OCT) to 3-dimensionally characterize the optic nerve head (ONH) in peripapillary scleral bowing in non-highly myopic healthy eyes. DESIGN: Cross-sectional, multicenter study. METHODS: A total of 362 non-highly myopic (+ 6 diopters [D] > spherical equivalent > - 6D) eyes of 362 healthy subjects from 20-90 years old underwent OCT ONH radial B-scan imaging. Bruch's membrane (BM), BM opening (BMO), anterior scleral canal opening (ASCO), and the peripapillary scleral surface were segmented. BMO and ASCO planes were fit, and their centroids, major axes, ovality, areas and offsets were determined. Peripapillary scleral bowing was characterized by 2 parameters: peripapillary scleral slope (ppSS) of 3 anterior peripapillary scleral segments (0-300, 300-700, and 700-1,000 mu m from the ASCO centroid); and ASCO depth relative to a peripapillary scleral reference plane (ASCOD-ppScleral). Peripapillary choroidal thickness (ppCT) was calculated relative to the ASCO as the minimum distance between the anterior scleral surface and BM. RESULTS: Both ppSS and ASCOD-ppScleral ranged from slightly inward through profoundly outward in direction. Both parameters increased with age and were independently associated with decreased ppCT. CONCLUSIONS: In non-highly myopic healthy eyes, outward peripapillary scleral bowing achieved substantial levels, was markedly increased with age, and was independently associated with decreased peripapillary choroidal thickness. These findings provide a normative foundation for characterizing this anatomy in cases of high myopia and glaucoma and in eyes with optic disc tilt, torsion, and peripapillary atrophy. (C) 2020 Elsevier Inc. All rights reserved.
Gesehen am 15.01.2021